INTERDISCIPLINARY RELATIONS AND DIRECTIONS OF LEARNING PROBLEMS OF DIFFERENTIAL OPERATORS - Birgebaev А.Б.; Sakhabaeva А.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Interdisciplinary communication provides effective formation of scientific concepts and a deep understanding of the theory being studied. It also promotes the integration of science, the development of links between different branches of knowledge, and the determination of the place of disciplines in the system of science. It is known that many naturalization problems are reduced to differential equations. In a word, mathematical culture can be mastered by mathematical qualification, skill, intuition, using the problem of differentiation of differential operators in its solution. The demonstration of the productive use of mathematical concepts in other sciences occupies an important place in the education of world perception. The value of mathematical modeling, i.e. differential equation, is that its concepts, formulas, methods, algorithms can be used by technical engineers, chemists, biologists, economists and representatives of other sciences, with the exception of mechanics and physicists. Currently, mathematical modeling is considered as a new universal component of the methodology of any science.